2020
DOI: 10.2147/cmar.s282181
|View full text |Cite
|
Sign up to set email alerts
|

NUCKS1 Promotes Proliferation, Invasion and Migration of Non-Small Cell Lung Cancer by Upregulating CDK1 Expression

Abstract: Background Non-small cell lung cancer (NSCLC) is a predominant type of lung cancer with a high mortality rate. Objective The aim of this study is to investigate the roles of nuclear casein kinase and cyclin-dependent kinase substrate 1 (NUCKS1) in NSCLC and to identify the potential mechanisms. Materials and Methods The expression of NUCKS1 in several NSCLC cells was detected firstly. Then, NUCKS1 was overexpressed or silenced in both A549 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“… 39 Furthermore, NUCKS1 elevation interacted with CDK1, thereby accelerating tumor growth in NSCLC. 23 Herein, NUCKS1 was upregulated in NSCLC, and NUCKS1 upregulation offset the inhibiting impact of miR‐433‐3p elevation on NSCLC cell proliferation, migration, invasion, and the Warburg effect. Importantly, circ_0008037 could regulate NUCKS1 expression by adsorbing miR‐433‐3p.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“… 39 Furthermore, NUCKS1 elevation interacted with CDK1, thereby accelerating tumor growth in NSCLC. 23 Herein, NUCKS1 was upregulated in NSCLC, and NUCKS1 upregulation offset the inhibiting impact of miR‐433‐3p elevation on NSCLC cell proliferation, migration, invasion, and the Warburg effect. Importantly, circ_0008037 could regulate NUCKS1 expression by adsorbing miR‐433‐3p.…”
Section: Discussionmentioning
confidence: 84%
“… 20 Recent studies have revealed that NUCKS1 act as an oncogene in gastric cancer, 21 hepatocellular carcinoma, 22 and NSCLC. 23 However, the regulatory network related to NUCKS1 in NSCLC is still indistinct.…”
Section: Introductionmentioning
confidence: 99%
“…CDK1 is mainly responsible for promoting G1/S phase and G2/M switching (14). Previous studies have also shown that CDK1 is abnormally expressed in a variety of tumors (15,16). Based on the GSEA method, the relationship between the expression level of CDK1 in the RB tissues and the cell cycle was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…NUCKS1 also exhibits oncogenic properties, and its overexpression, correlating with poor patient prognosis, has been reported in a number of cancers 33 38 . Furthermore, NUCKS1 depletion inhibits—while its overexpression promotes—xenograft tumour growth 18 , 39 , 40 , suggesting a direct role in tumourigenesis.…”
Section: Introductionmentioning
confidence: 99%